Efficacy of repeat doses of avatrombopag: a case series - Saab, Sammy; McDaniel, Terina K.; Bau, Sherona N.; Patel, Radhika P. (Digestive Medicine Research, 2019)
Thrombocytopenia is a common hematologic complication in patients with chronic liver disease. Thrombocytopenia places these patients at risk who undergo invasive procedures. Patients with cirrhosis often require repeat procedures. Patients with chronic liver disease and platelet counts below 50,000/µL who underwent repeat doses of avatrombopag (AVA) prior to multiple invasive procedures. Changes in platelet count were measured with each course of AVA. The need for platelet transfusion and adverse events from AVA were noted. Four patients underwent repeat AVA dosing. The mean [± standard deviation (SD)] age of the patients who underwent repeat dosing was 65 (±29) years. The mean (± SD) platelet count prior to the procedure was 38,250 (±5,679)/µL, and the mean increase of platelets was 52,000 (±33,000)/µL. Similarly, the mean (± SD) increase after the repeat administration was 51,000 (±31,000)/µL. No patient required platelet transfusion or rescue therapy. No adverse effects were reported. Repeat use of AVA continues to be an effective tool to minimize the use of platelet transfusions in patients undergoing invasive procedures who have chronic liver disease. Repeat dosing does not appear to reduce AVA efficacy.